ANALISIS MANAJEMEN UNIT USAHA PESANTREN MA’HAD DARUT TAUHID (MADAD) DI DESA RAPA LAOK KECAMATAN OMBEN KABUPATEN SAMPANG - Pratama, Angga; Qamariyah, Siti (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2021)
The low understanding and application of the management of the Pesantren Business Unit, has an impact on the income and progress of the Ma'had Darut Tauhid Islamic Boarding School (MADAD) which has an impact on the economic sustainability of the Islamic Boarding School. So to find out how much management is implemented, it is necessary to do research. This study uses a qualitative descriptive method. The result, Many Pesantren Business Unit officers still do not know the management system. So it is necessary to be equipped with continuous training, in order to improve the quality of work and provide benefits for the business unit of the Ma'had Darut Tauhid Islamic boarding school (MADAD), especially in the field of management with great hope that if the management is carried out correctly and appropriately it can increase the income and welfare of the pesantren at the same time. all aspects related to pesantren.